Exploring the impact of time allocation on students’ writing performance: A quantitative study - Ramadhani, Dwiansari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Many educational institutions have been conducting writing assessments to measure students’ ability in writing, yet little is known about whether time restriction and learning strategies are contributing factors to students’ performance. In Indonesian educational institutions, writing assessments serve as a means to measure students’ proficiency in articulating thoughts in the target language, providing teachers with insights into their linguistic ability. The objective of this study is to determine whether allocating extra time for timed academic essays will substantially enhance the quality of students' writing. Additionally, this study seeks to uncover the correlation between students' L2 learning strategies and their writing performance. This study used a quantitative design. The main instruments were questionnaires and writing tests collected at two parallel classes of a private university in Indonesia, comprising of 50 students in total as the study participants. The quantitative methods used independent t-tests and Spearman’s rho correlation to analyze the data. The result showed that time limit had a significant effect on writing performance (t(34.6)= 3.185, p= .003). Another result indicated minimal to no correlation between writing scores and autonomous learning practices. In conclusion, this study offers valuable and practical implications in the writing assessment industry that there should be a re-evaluation in the administration of writing assessment in educational institutions in Indonesia that truly reflects students’ writing ability.